Efeitos de substitutos de sal, gordura e antioxidante sintético na qualidade de mortadelas - Costa, Sonnalle Silva (2019)
Mortadellas are meat products much appreciated and consumed for their pleasant taste and low commercial value, but commonly feature high levels of sodium and saturated fat in their composition. Due to the increasing consumer demand for healthier products, researchers and industries have been looking for strategies to reduce these nutrients in meat products. The objective of this study was to evaluate the effect of simultaneous partial replacement of sodium chloride (NaCl) by potassium chloride (KCl) and pork-back fat by a pre-emulsified blend of olive, linseed and fish oils, as well as the effect of the addition of synthetic, butyl hydroxytoluene (BHT), and natural (rosemary extract) antioxidants in the quality of reformulated mortadella. In a first experiment, to evaluate the effect of the factors KCl and pre emulsified oil blend on the sensory properties of mortadella, a Central Composite Rotational Design (CCRD) with two-level and two-factor (22 ) plus four axial points and the central point was employed, which was repeated three times, resulting in a total of eleven formulations. Along with a traditional formulation (control), CCRD formulations were analyzed by trained panelists using the Quantitative Descriptive Analysis (QDA) methodology. From the results of the QDA, an optimized mortadella formulation was defined. In the second experiment, in addition to a traditional mortadella formulation (MCon), three other mortadella formulations were prepared based on the optimized formulation in the first experiment: reformulated mortadella without the addition of antioxidants (MMix), reformulated mortadella with the addition of BHT to the oil blend ( MMix BHT) and reformulated mortadella with the addition of rosemary extract to the oil blend (MMix Rosemary), in which changes in physicochemical characteristics and oxidative stability were evaluated during cold storage at 4 °C. In the first experiment, it was verified that the modifications made in some CCRD formulations resulted in differences in the pink color, characteristic mortadella flavor, condiment flavor and saltiness descriptors in relation to the control. However, the addition of KCl and pre-emulsified oil blend at the central point levels allowed the obtaining of mortadella with sensory characteristics similar to the control product and reduced total lipid content and saturated fatty acid fraction, decreased NaCl content and increased content of polyunsaturated fatty acids in line with health recommendations. In the second experiment, it was observed that the reformulated mortadellas featured slight changes in color and instrumental texture and increased lipid oxidation during storage compared to the control mortadella. However, the addition of rosemary extract to the oils provided to the reformulated products (MMix Rosemary) oxidative stability superior or similar to the control, in most periods evaluated, unlike synthetic antioxidant, presenting an effective strategy to slow the lipid oxidation in the product. Thus, considering the evaluated aspects, the simultaneous use of partial substitutes for salt and pork-back fat, associated with the incorporation of a natural antioxidant (rosemary extract) in the oil blend can be considered promising alternatives to obtain mortadella with better nutritional quality.